Pregnancy Outcomes in the Superobese, Stratified by Weight Gain Above and Below Institute of Medicine Guidelines. Issue 4 (December 2015) - Swank, M.L.; Marshall, N.E.; Caughey, A.B.; Main, E.K.; Gilbert, W.M.; Melsop, K.A.; Chung, J.H.
Abstract : ( Obstet Gynecol . 2014;124(6):1105–1110)